2016
DOI: 10.1007/s12185-016-2054-7
|View full text |Cite
|
Sign up to set email alerts
|

Iron-induced epigenetic abnormalities of mouse bone marrow through aberrant activation of aconitase and isocitrate dehydrogenase

Abstract: Iron overload remains a concern in myelodysplastic syndrome (MDS) patients. Iron chelation therapy (ICT) thus plays an integral role in the management of these patients. Moreover, ICT has been shown to prolong leukemia-free survival in MDS patients; however, the mechanisms responsible for this effect are unclear. Iron is a key molecule for regulating cytosolic aconitase 1 (ACO1). Additionally, the mutation of isocitrate dehydrogenase (IDH), the enzyme downstream of ACO1 in the TCA cycle, is associated with epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Iron-overloaded Tibetans have higher methylation levels Single-base methylation of iron-overloaded Tibetans was deciphered by WGBS. The methylation level of the whole genome in the TH group was about 2.26%, and the proportion of mCG, mCHH and mCHG in the TH group was slightly higher than that in the TL group, which was consistent with the results observed in iron overload mice, where iron overload can enhance genomic DNA methylation (Yamamoto et al, 2016). The ratio and level of CG methylation types in the genome is the highest, which is consistent with previous findings in humans (Rademacher et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Iron-overloaded Tibetans have higher methylation levels Single-base methylation of iron-overloaded Tibetans was deciphered by WGBS. The methylation level of the whole genome in the TH group was about 2.26%, and the proportion of mCG, mCHH and mCHG in the TH group was slightly higher than that in the TL group, which was consistent with the results observed in iron overload mice, where iron overload can enhance genomic DNA methylation (Yamamoto et al, 2016). The ratio and level of CG methylation types in the genome is the highest, which is consistent with previous findings in humans (Rademacher et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, DNAm may change the susceptibility to diseases or phenotypic traits of normal people. Iron metabolism is closely associated with DNAm, and the level and status of iron affect DNAm (Yamamoto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] DNA methylation is increased in bone marrow of male C57BL/6N mice after a 5‐day FeDx injection. [ 24 ] FXR expression is regulated by two DNA methyltransferases (DNMTs; DNMT1 and 3B) in colon cancer cells. [ 21 ] Our data showed that knockdown of DNMT1 , but not DNMT3B , significantly diminished the suppressive effect of FAC on FXR in HepG2 and Huh7 cells (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Although barely nonstatistically significant, this result may deserve further studies because iron has not been previously identified as a potential risk factor for PDAC. Iron is a known carcinogen: it promotes mitosis, interferes with MnSOD functionalism, activates xanthine oxidase causing oxidative damage, inhibits apoptosis, and increases telomerase activity (Toyokuni ; Yamamoto et al ). As with iron, higher concentrations of vanadium were associated with a higher probability of having a PDAC without KRAS mutations.…”
Section: Discussionmentioning
confidence: 99%